Challenging orthodoxies: Understanding poverty in pastoral areas of East Africa - Little, P.D.; McPeak, J.G.; Barrett, Christopher B.; Kristjanson, Patricia M. (Wiley, 2008)
Understanding and alleviating poverty in Africa continues to receive considerable attention from a range of diverse actors, including politicians, international celebrities, academics, activists and practitioners. Despite the onslaught of interest, there is surprisingly little agreement on what constitutes poverty in rural Africa, how it should be assessed, and what should be done to alleviate it. Based on data from an interdisciplinary study of pastoralism in northern Kenya, this article examines issues of poverty among one of the continent's most vulnerable groups, pastoralists, and challenges the application of such orthodox proxies as incomes/expenditures, geographic remoteness, and market integration. It argues that current poverty debates `homogenize' the concept of `pastoralist' by failing to acknowledge the diverse livelihoods and wealth differentiation that fall under the term. The article concludes that what is not needed is another development label (stereotype) that equates pastoralism with poverty, thereby empowering outside interests to transform rather than strengthen pastoral livelihoods.